Effect of glycerol and dimethylformamide cryoprotectants on buck Etawah Crossbreed frozen semen using modified tris diluents. - Ariantie OS; Yusuf TL; Sajuthi D; Arifiantini RI (Indonesian Center for Animal Research and Development (ICARD), 2013)
A cryoprotectan is component that must be present in a cryopreservation medium to minimize the physical and chemical stresses resulting from the cooling, freezing and thawing of sperm cells. This study was carried out to determine the effect of glycerol (G) and dimethylformamide (DMF) as cryprotective agent in tris-egg yolk (TEY) trehalose (T) and tris-soya (TS) raffinose (R) diluents. Semen were collected from three sexually mature bucks using artificial vagina, evaluated and divided into four aliquot. Each of them was diluted with TEY suplemented with 50 mM trehalose and TS supplemented with 50 mM raffinose, added with glycerol or DMF 4% (v/v). Diluted semen was packed in minitube straw (100 x 106 sperm/0.25 mL) and equilibrated for 4 hours at 5°C, then freeze in N2 vapor for 10 minutes in styrofoam box and stored in liquid N2 container (-196) until futher evaluation. Progressive motility, viability and plasma membrane intact were evaluated after thawed at 37°C for 30 seconds factorial experimental design (2 x 2) was used in this study. The sperm motility in TEYTG was significantly higher (65.07±5.38%) compared to TEYTDMF (61.67±5.55%). In contrast sperm diluted with TSRDMF indicated better motility (42.22±8.13%) than TSRG (39.07±5.38%). It was concluded that cryoprotectant had different effect on different diluents. Key Words: Buck Etawah Crossbreed, Cryoprotectant, Diluent, Frozen Semen